2020
DOI: 10.4018/ijthi.2020010102
|View full text |Cite
|
Sign up to set email alerts
|

Can Cognitive Style Predict Adoption of an Emerging Technology?

Abstract: Understanding how individuals recognize an emerging technology can have a profound impact on how successfully the technology is adopted. The authors look into how people with different cognitive styles interpret a new technology and arrive at different beliefs of the same technology, which influences the recognition and acceptance of the technology. An experiment was conducted to test whether an individual's cognitive style impacts their beliefs and intention to use RFID, an emerging technology. The study sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Considering the complex nature of human behaviour, it is important to identify and decide on the attitudes that are relevant for specific behaviour, yet the TPB fails to offer a detailed account of such variations in attitudes as intended for this study. Nonetheless, some studies highlighted some of these attributes and suggested that differences in attitudes significantly contribute to the difference in people's behavioural intentions to adopt energy technologies (Chae et al, 2020;Davern et al, 2012;LaMorte, 2019).…”
Section: Theoretical Review 21 Theory Of Planned Behaviour -Tpbmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the complex nature of human behaviour, it is important to identify and decide on the attitudes that are relevant for specific behaviour, yet the TPB fails to offer a detailed account of such variations in attitudes as intended for this study. Nonetheless, some studies highlighted some of these attributes and suggested that differences in attitudes significantly contribute to the difference in people's behavioural intentions to adopt energy technologies (Chae et al, 2020;Davern et al, 2012;LaMorte, 2019).…”
Section: Theoretical Review 21 Theory Of Planned Behaviour -Tpbmentioning
confidence: 99%
“…Given the numerous functionalities of most solar energy technologies, people in the USA and Chile use these technologies based on their specific needs, awareness, and ability to reduce costs, increase efficiency, and flexibility (Rojas-M endez et al, 2017). Not all people appreciate these benefits in the same way, implying that some people may not be psychologically ready to adopt those technologies, especially if they are considered sophisticated, risky, and less compatible (Chae et al, 2020).…”
Section: Specific Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the original conceptualization of CSs as patterns of adaptation to environmental demands (Klein, 1954; Witkin et al, 1962) has often been overlooked, leading to the proliferation of attempts to define CS as ‘preferences’ or ‘ways’ of information processing, and, as a result, to ongoing debates about the usefulness of the concept. While some researchers have argued that no scientific evidence indicates CSs might produce better learning (Nancekivell et al, 2020, 2021; Riener & Willingham, 2010), others suggested a multidimensional effect of CSs on every aspect of our lives, such as providing insights into composing effective teams (Aggarwal & Woolley, 2019), influencing learners' attitudes towards technology (Chae et al, 2020), explaining political beliefs (Yilmaz & Saribay, 2018) and serving as a reliable predictor of academic achievement (Köseoglu, 2016) and creative performance (Kozhevnikov et al, 2013, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This research focuses only on SaaS based cloud services. SaaS cloud is defined as "application or function made available to customers, by the provider, through various devices like web browser or program interfaces" (Wease et al, 2018, p.449).The Software as a Service (SaaS) based cloud storage drives like Google Drive, iCloud, DropBox, Microsoft OneDrive, or Office 365, …etc., which are safe to store and access the data from anywhere, at any place without any complexity (Kalim et al, 2020, Chae, et al, 2020, Chege et al, 2020, Reilly and Milner, 2020, Sahu and Khandekar, 2020, Kani et al, 2020.…”
Section: Introductionmentioning
confidence: 99%